Prevalence of primary renal diseases among patients on maintenance haemodialysis: a hospital based study (KYAMC Journal, 2013)
Background: Chronic Kidney Disease (CKD) is the third most common non-communicable disease throughout the world. Studies have shown that kidney patients suffer much from hypertension, diabetes than glomerulonephritis. Many of these CKD patients ultimately terminate to End Stage Renal Disease (ESRD) when life is not sustainable unless hemodialysis is initiated. Aim: The aim of this study was to identify primary renal disease leading to ESRD requiring hemodialysis and associated co-morbidities. Material and methods: Data was collected purposively from selected six hemodialysis centers. Patients were selected purposively who were available at the time of interview. Data was collected on working days at three shifts After taking informed consent from patients the pre-tested questionnaire was filled up by taking general history, family history, socioeconomic condition, drug history and available records were reviewed for collecting previous biochemical parameters. All entered data were analyzed by using SPSS program version 13.0. Result: Among total 393 subjects, male was 247(63%) and female 146 (37%). Majority were middle aged. Glomerulonephritis were found to be the leading cause of End Stage Renal Disease (ESRD) (50.4%), followed by diabetes in 31.1%, Poly Cystic Kidney Disease (PKD) 5.3%, Renal Stone in 3.7% and rest other. Among the study population hypertension was the most common co morbidity disease (63%) followed by ischemic heart disease and Cerebrovascular accidents. Conclusion: Glomerulonephritis was found to be the leading cause of End Stage Renal Disease (ESRD) and diabetic nephropathy was the second common cause. Hypertension was the most common associated co morbid disease. To evaluate the actual disease pattern a large scale study is required to find the outcome of haemodialysis patients.DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13262KYAMC Journal Vol.2(2) January 2012, 182-186